The Function of circRNA-0047604 in Regulating the Tumor Suppressor Gene DACH1 in Breast Cancer. (20th January 2022) - Zhao, Bingkun; Zhou, Rong; Ji, Changle; Liu, Diya; Wu, Tianqi; Xu, Hui; Lan, Dongmei; Yao, Chao; Xu, Yuanzhi; Fang, Lin
Abstract : Breast cancer is the most common cancer among females. Dachshund Homolog 1 (DACH1) gene is regarded as an important tumor suppressor gene in breast cancer which plays an important regulatory role in the development disease progression, particularly in carcinomas. Circular RNAs (circRNAs) and microRNA (miRNA), regarded as a novel group of noncoding RNAs, are always involved in regulating gene expression. In this work, hsa_circ_0047604 expressed lower in breast cancer tissue and played the role of sponge of miR-548o. By this way, hsa_circ_0047604 could upregulate DACH1 to inhibit breast cancer. In conclusion, this study revealed that hsa_circ_0047604 acted as a tumor suppressor and regulated breast cancer progression via hsa_circ_0047604–miR-548o–DACH1 axis, which might provide a therapeutic method for breast cancer.